Antihyperalgesia effect of AMP-activated protein kinase (AMPK) activators in a mouse model of postoperative pain. Issue 8 (21st June 2019) - Das, Vaskar; Kroin, Jeffrey S; Moric, Mario; McCarthy, Robert J; Buvanendran, Asokumar
Abstract : Background and objectives: AMP-activated protein kinase (AMPK) activator drugs decrease hypersensitivity in mice with pain. This study examines if postsurgery treatment with the prototype AMPK activator metformin and a new mechanism-specific AMPK activator, O304, after plantar hindpaw incision in mice, would reduce mechanical hypersensitivity and produce changes in the AMPK pathway in the dorsal root ganglion (DRG). Methods: To create postoperative pain, an incision was made in the left plantar hindpaw. Animals were randomized into four oral gavage drug treatment groups (n=8/group): (1) vehicle, (2) metformin 200 mg/kg, (3) O304 200 mg/kg and (4) O304 200 mg/kg plus metformin 200 mg/kg. Drug gavages were performed 4 hours postsurgery and were repeated for 3 days. Mechanical hypersensitivity was measured with von Frey filaments. Changes in phosphorylated AMP-activated protein kinase alpha subunit, phosphorylated mechanistic target of rapamycin and phosphorylated eukaryotic initiation factor 2 alpha in DRG neurons were examined by immunohistochemistry. Results: O304 or metformin increased von Frey thresholds (reduced mechanical hypersensitivity) in plantar incision mice versus vehicle-treated incision mice between days 1 and 4 (difference of mean area under the curve, O304: 2.24 g*day; 95% CI of the difference 0.28 to 4.21, p=0.011; metformin: 2.56 g*day; 95% CI of the difference 1.71 to 3.41, p<0.001). The drug combination further elevated von Frey thresholds. In the vehicle-treated group, the AMP-activated protein kinase alpha subunit was downregulated and mechanistic target of rapamycin and eukaryotic initiation factor 2 alpha were upregulated in DRG neurons; these deficits were reversed by the AMPK activator treatments. Conclusions: Early treatment with the mechanism-specific AMPK activator O304 or the prototype AMPK activator metformin reduces mechanical hypersensitivity in a postoperative pain model in mice. These drugs also normalize the AMPK pathway in the DRG.